Genetic Diversity of Indonesian Swamp Buffalo Based on Microsatellite Markers - F. Saputra; Jakaria Jakaria; A. Anggraeni; C. Sumantri (Faculty of Animal Science, Bogor Agricultural University, 2020)
Indonesia has high genetic resources of local swamp buffalo with good adaptation across regions. However, these animals decline in both population and genetic quality. This research was conducted to study the genetic diversity of Indonesian swamp buffalo. A total of 199 DNA samples (swamp buffalo) from seven provincial populations were used in this study. Genetics identification used three microsatellite markers (CSSM66, ILSTS61, and ILSTS17). Microsatellites were visualized by Polyacrylamide Gel Electrophoresis (PAGE) 10% with silver staining method. Microsatellite data were analyzed using GenAlEx 6.41, Cervus 3.0, and POPTREE2 software. The results showed that a total of 9 alleles were found from the three loci. ILSTS61 had a high PIC (Polymorphism Information Content) compared to the other loci. The high observed heterozygosity of ILSTS61 was found in swamp buffalo from Riau Province, while the Ho value of ILSTS17 ranged from 0.000 to 0.170. This study identified two clusters for Indonesian swamp buffalo, i.e., cluster I (Aceh, North Sumatra, and Riau) and cluster II (Banten, Central Java, West Nusa Tenggara, and South Sulawesi). The two major divergent directions are considered in Indonesia swamp buffaloes across the observed provinces.